Synovial juxtafacet cyst of the spine presenting as radiculopathy - Mohd Nasir, Mohd Nizlan; K., Selvakumar; Looi, L. M.; R., Kunasegaran (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
Juxtafacet cyst of the spine is a rare occurrence. Reports have described them as synovial cysts; ganglion cyst; extradural cysts as well as degenerative cysts of the spine. Patients may present with radicular pain, motor deficits, sensory disturbances, cauda equine syndrome and even myelopathy. Lumbar juxtafacet cysts may be confused clinically with prolapsed intervertebral disc or other conditions involving nerve root compression such as arachnid cysts, ependymal cysts, dermoid cysts or teramatous cycts. In the case of the juxtafacet cysts, surgical excision is usually curative. We report a case of spinal synovial juxtafacet cysts found intraoperatively in a case that was preoperatively diagnosed as prolapsed intervertebral disc. Synovial juxtafacet cysts of the spine should be considered as one of the differential diagnoses in patients, especially in older patients, presenting with nerve root compression.